Knowledge Management Practices in Enhancing Academic Output: A Study of Indonesian Islamic Universities - Niam, Khoirun; Huda, Muhammad Nuril; Sulanam, Sulanam; Ridwan, Auliya (Ulumuna, 2023)
This study examines knowledge management strategies employed by Islamic universities in Indonesia to boost academic knowledge production. It explores the policies designed to support lecturers and students in producing and publishing scholarly work that is accessible and recognized within the scientific community. Focusing on five state Islamic Higher Education institutions (PTKIN) selected for their Sinta 2.0 ranking, the research identifies unique and standard policies across these universities to enhance knowledge output. Findings reveal that each PTKIN implements specific strategies to increase knowledge production and values contributions to reputable international journals. These strategies include providing resources and support for knowledge creation rooted in a shared foundation of program improvements directed by the Ministry of Religious Affairs. The study highlights how these universities adapt and extend existing initiatives to meet their unique needs, demonstrating the effectiveness of tailored knowledge management practices in fostering academic excellence.